2016
DOI: 10.1128/jvi.00805-16
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-Specific Chimeric Antigen Receptors Based on Broadly Neutralizing Antibodies

Abstract: Although the use of chimeric antigen receptors (CARs) based on single-chain antibodies for gene immunotherapy of cancers is increasing due to promising recent results, the earliest CAR therapeutic trials were done for HIV-1 infection in the late 1990s. This approach utilized a CAR based on human CD4 as a binding domain and was abandoned for a lack of efficacy. The growing number of HIV-1 broadly neutralizing antibodies (BNAbs) offers the opportunity to generate novel CARs that may be more active and revisit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 31 publications
1
95
0
Order By: Relevance
“…PGT128 CAR T cells, in contrast, exhibited lower rates of CD137 expression after co-culture with HIV pos targets and appeared to clear HIV pos cells less well than other HIV-CAR T cells but produced cytokines after stimulation with cells expressing an alternative HIV envelope. Ali et al 58 recently compared the potency of bNAb-based HIV CARs against HIV-1 NL4-3 -infected T2 cells and found the CAR based on the PGT128 bNAb to be the www.moleculartherapy.org least effective, whereas that based on the 10E8 bNAb was the most potent. Here we observed that 10E8 HIVCAR T cells exhibited an activation profile that varied between donors and killed less potently than PGT145-and VRC07-523-HIVCAR T cells in our target cell assays.…”
Section: Discussionmentioning
confidence: 99%
“…PGT128 CAR T cells, in contrast, exhibited lower rates of CD137 expression after co-culture with HIV pos targets and appeared to clear HIV pos cells less well than other HIV-CAR T cells but produced cytokines after stimulation with cells expressing an alternative HIV envelope. Ali et al 58 recently compared the potency of bNAb-based HIV CARs against HIV-1 NL4-3 -infected T2 cells and found the CAR based on the PGT128 bNAb to be the www.moleculartherapy.org least effective, whereas that based on the 10E8 bNAb was the most potent. Here we observed that 10E8 HIVCAR T cells exhibited an activation profile that varied between donors and killed less potently than PGT145-and VRC07-523-HIVCAR T cells in our target cell assays.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described the generation of HIV-1-specific CAR-T cells by connection of an extracellular antigenbinding domain to intracellular T cell activation domains (e.g., CD3 and CD28). The former can be a single-chain variable fragment (scFv) (26)(27)(28)(29)(30) or a natural molecule, such as CD4 (26,27,(31)(32)(33)(34)(35)(36), capable of directly inducing the death of cells expressing the viral envelope glycoprotein (Env). However, it remains to be determined whether these CAR-T cells can be used to kill the reactivated HIV-1 latently infected cells from the infected individuals receiving suppressive cART.…”
mentioning
confidence: 99%
“…[30][31][32] The use of this CD4fCAR has important advantages, in that it has been found to be a safe reagent in multiple long-term clinical trials with over 500 patient years of clinical safety data 33,34 and this is strong evidence that it does not induce cytokine storms that have been an unwanted element with other CAR-based approaches in treating malignancies. 35,36 It is also unlikely to generate escape variants of HIV envelope as the loss of CD4 binding of an escape variant will likely have a dramatic effect on viral fitness.…”
Section: Fig 1 Hiv-specific Chimeric Antigen Receptors (Cars)mentioning
confidence: 99%
“…We and others have done extensive testing of the antiviral function of CD8 + T cells transduced with CD4f CAR, finding that transduced cells are capable of killing HIV-infected cells and suppressing viral replication [30][31][32]34,37 and (unlike the HIV-specific TCR) that this activity is independent of HLA-I molecules. 38 CARs can also function in CD4 + T cells to act as HIV-1-specific helper cells.…”
Section: Fig 1 Hiv-specific Chimeric Antigen Receptors (Cars)mentioning
confidence: 99%
See 1 more Smart Citation